Spatial complexity and interactions in the FDI attractiveness of regions - Laura Resmini; Laura Casi (European Regional Science Association (ERSA), 2013)
This study investigates the factors that drive the distribution of foreign direct investments (FDI) into European regions, trying to disentangle the spatial complexity of this economic relationship. In particular, we argue that regions' capacity to attract FDI is affected by own-country effects, which can take two different forms: the first relates to the relative performance of the country a region belongs to in Europe (between country effect) while the second concerns the relative performance of regions' within their own countries (within country effect). We find that own country effects exist, though the within country effect is weaker than the between country effect. The absolute performance of countries is able to affect that of their own regions along many axes, on top of region?s absolute performance. When modelling spatial interactions and spillovers, it also emerges a clear pattern of territorial competition among regions in attracting FDI.
Keywords: 330; FDI; spatial effects; regions' competitiveness